Thermal Neutron Absorption in Printed Circuit Boards - Platt, Simon P.; August, Shaun; MacLeod, Michael; Anderson, Michael J.; Cheneler, David; Monk, Stephen D. (IEEE transactions on nuclear science, 2021)
Measurements and simulations of thermal neutron attenuation by printed circuit boards (PCBs) are compared. Attenuation coefficients in typical epoxy-resin/glass-fiber substrate material can be as high as 2 cm −1 , corresponding to 27% attenuation by 1.6 mm of the substrate. Attenuation is attributed to neutron scattering off hydrogen in the resin acting in synergy with absorption by boron in the glass; this effect is substantially greater than that estimated from absorption by boron alone. Design of thermal neutron detector assemblies should take this attenuation into account and may require board thickness to be minimized or specialized substrate materials to be used.